2017
DOI: 10.1080/14767058.2017.1289163
|View full text |Cite
|
Sign up to set email alerts
|

Placenta previa and maternal hemorrhagic morbidity

Abstract: Placenta previa is an independent risk factor for maternal hemorrhagic morbidity. Some risk factors are modifiable, but many are intrinsic to the clinical scenario.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 20 publications
(29 reference statements)
1
74
0
2
Order By: Relevance
“…The recent case-control study from the NICHD/MFMU Network Cesarean Section Registry found general anaesthesia to be one of the main factors associated with maternal haemorrhage in women with placenta praevia. 86 Evidence level 2++…”
Section: Evidence Level 2àmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent case-control study from the NICHD/MFMU Network Cesarean Section Registry found general anaesthesia to be one of the main factors associated with maternal haemorrhage in women with placenta praevia. 86 Evidence level 2++…”
Section: Evidence Level 2àmentioning
confidence: 99%
“…85 A US case-control study from the National Institute of Child Health and Human Development (NICHD) Maternal-Fetal Medicine Units (MFMU) Network Cesarean Section Registry has shown that maternal haemorrhagic morbidity is more common in women with praevia (19% versus 7%, adjusted RR 2.6, 95% CI 1.9-3.5) and the main factors associated with maternal haemorrhage include pre-delivery anaemia, thrombocytopenia, diabetes and magnesium use. 86 Evidence level 2++…”
mentioning
confidence: 99%
“…The antenatal hemorrhage may lead directly to preterm labor, which even affects neonatal prognosis. Gibbins et al reported that placenta previa is an independent risk factor for maternal hemorrhagic morbidity, although it is not associated with placental adhesion [3].…”
Section: Introductionmentioning
confidence: 99%
“…The study by Gibbins et al . reported that the maternal mortality ratio is increased approximately threefold for women with placenta previa …”
Section: Introductionmentioning
confidence: 99%